A compact, practical photoreactor for multi-reaction arrays. Issue 9 (5th June 2022) - Brown, Gregory D.; Batalla, Daniel; Cavallaro, Cullen L.; Perez, Heidi L.; Wrobleski, Stephen T.; Sherwood, Trevor C.
Abstract : We report here the BMS-PR460: a photoreactor designed for multi-reaction arrays at various scales and temperatures with irradiation at 460 nm. Transformations of interest to pharmaceutical research have been performed to demonstrate reactor utility. Abstract : The Bristol Myers Squibb Photoreactor (BMS-PR) is a convenient, small-footprint platform that enables routine use of photochemical transformations in a variety of laboratory settings. These photoreactors have been engineered to safely irradiate multiple reaction vessels for array synthesis at various wavelengths and temperatures with a more practical setup than most other commercial photoreactors. The BMS-PR integrates seamlessly with standard laboratory equipment and incorporates a variety of attractive safety features. Herein we describe the BMS-PR460 device for irradiation of reactions at 460 nm using blue light-emitting diodes (LEDs) and highlight its application with photochemical reactions that may be useful in the discovery of novel drug molecules.